PEMETAAN KETERSEDIAAN RUANG TERBUKA HIJAU PUBLIK BERDASARKAN KEBUTIHAN OKSIGEN DI KOTA PAINAN - Try yani Haryani; Arie Yulfa (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to determine: (1) the extent of public green open space in Painan City, (2) the distribution of available public green open spaces in Painan City, (3) the size of the public green open space required by Painan City based on oxygen demand. This type of research is using a qualitative descriptive method which aims to reveal events or facts, circumstances, phenomena, variables and circumstances that occurred during the research by presenting what actually happened. The results of this study indicate that: (1) The area of ​​public green open space based on the area in Painan City is 321.70 ha. (2) Availability of public green open space based on oxygen demand in Painan Urban which is 390.10 ha which can be seen from three consumers such as population, motorized vehicles and livestock. (3) The area of ​​green open space currently available is 201.72 ha. So that the existing public green open space in Painan City currently still requires around 188.38 ha of green open space. Keywords: Public Green Open Space